2019
DOI: 10.5018/economics-ejournal.ja.2019-36
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time and labor productivity: a new economic view rooted from sociological perspective

Abstract: Most economists measure labor productivity based on activities conducted at places of work and do not consider leisure time in their calculations. In contrast, psychologists and sociologists argue that leisure has a positive role in the production process: leisure can improve individuals' labor productivity by affecting their self-development. Using empirical data from 21 OECD countries, this study finds that leisure time has a dual effect on labor productivity in terms of per capita per hour GDP. Moreover, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…The last independent test from this study, we found that the working hour variable had a positive and significant relationship to the labor productivity variable as indicated by the Pearson Chi-Square p-value of 0.000. This finding is in line with and supports the results of a study conducted by Cui et al (2019); Man & Ling (2014) and Lubis (2014) which found that working hours had a significant effect on labor productivity, the more hours worked the higher the productivity of the workforce and vice versa.…”
Section: Simultaneous Test Of Model Estimation Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The last independent test from this study, we found that the working hour variable had a positive and significant relationship to the labor productivity variable as indicated by the Pearson Chi-Square p-value of 0.000. This finding is in line with and supports the results of a study conducted by Cui et al (2019); Man & Ling (2014) and Lubis (2014) which found that working hours had a significant effect on labor productivity, the more hours worked the higher the productivity of the workforce and vice versa.…”
Section: Simultaneous Test Of Model Estimation Resultssupporting
confidence: 91%
“…Finally, the working hour variable with the category of more than 7 hours per day has a significant effect and has a greater opportunity to increase labor productivity, which is 0.251 compared to less than 7 hours per day. These findings are in line with and support the findings of study conducted by Cui et al (2019); Man & Ling (2014) and Lubis (2014) which found that working hours had a significant effect on labor productivity.…”
Section: Independent Test Between Independent and Dependent Variablesupporting
confidence: 92%
“…Celbis and Turkeli had shown that at the country level, innovation exhibits diminishing returns on work hours [50]. A similar relationship between leisure time and productivity in general is observed by Cui et al [51]. We also assume that innovative performance does not increase linearly with respect to the number of work hours, but that there is some sort of inverted U-shape relationship.…”
Section: Theoretical Backgroundmentioning
confidence: 58%
“…The income domain is concerned with decision making power over the allocation of income whereas leadership concerns one's ability to lead e.g., in common interest groups and religious organizations. Lastly, the time domain is about allocation of one's time between farm activities and non-farm activities that may be high paying as well as leisure that has been found to have a positive and significant effect on labor productivity ( Cui et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%